ROLE OF SUSTAINED SYMPATHETIC OVERACTIVATION IN THE DEVELOPMENT OF STRUCTURAL AND FUNCTIONAL MYOCARDIAL CHANGES IN HEART FAILURE - O. E. OSADCHII (Кубанский научный медицинский вестник, 2018)
Heart failure is associated with profound sympathetic overactivation, which initially develops as an adaptive effect that supports cardiac contractile function. Nevertheless, in the long term, sympathetic activation promotes detrimental myocardial changes, and therefore contributes to systolic dysfunction and poor clinical prognosis. The current knowledge about the mechanisms of these maladaptive effects largely stems from the animal studies that utilized a model of heart failure induced by chronic administration of adrenergic agonists. In this model, sustained adrenergic overactivation was found to induce cardiac hypertrophy owing to the increased protein synthesis in cardiac myocytes, and to promote myocardial fibrosis by stimulating collagen production in cardiac fibroblasts. Catecholamines also produce toxic effects leading to the myocyte cell death via necrosis and apoptosis. Systolic dysfunction in the setting of adrenergic overactivation is partly attributed to the eccentric ventricular chamber remodeling, an effect related to the increased activity of matrix metalloproteinases which digest cross-linked collagen, and promote myocyte slippage. At the cellular level, cardiac contractile failure is linked to the impaired calcium handling. Beta-adreneregic stimulation causes hyperphosphorylation of the ryanodine receptor (RyR2) via cAMP-protein kinase A-dependent mechanism, which increases RyR2 open probability, and hence contributes to the calcium leakage, resulting in depleted sarcoplasmic reticulum calcium stores. This change is further exacerbated owing to the decreased SERCA2a expression in failing cardiac myocytes, which impairs sarcoplasmic reticulum calcium uptake in diastole. Overall, myocardial structural changes upon sustained adrenergic overactivation are related to the increased activity of the renin-angiotensin-aldosterone system, stimulation of the myocardial growth factors, and increased expression of cytokines. The adrenergic cellular growth-promoting effects are mediated through the mitogen-activated protein kinase signaling pathway, transient up-regulation of the immediate-early genes, and activation of transcription factors. These effects translate to the increased synthesis of contractile proteins and their assembly into the organized sarcomeric units in cardiac myocytes.